Pleistocene steppe-tundra insect communities of Beringia - Svetlana Kuzmina (Arctic, Antarctic, and Alpine Research)
The fossil insect fauna of Beringia contributes to our knowledge of the unique Pleistocene steppe-tundra biota. The Beringia insect database facilitated an ecological analysis and comparison of entomofaunas between Western and Eastern Beringia. The list of key species overlaps only partially. Among steppe indicators, there are no common species at all. Two closely related species of pill beetles of the genus Morychus existed in the steppe-tundra in parallel and occupied similar ecological niches, but in Western Beringia, these taxa played a more dominant role. In Western Beringia, there are more steppe indicators, including weevils of the tribe Cleonini, and their role in the fossil fauna is more significant. In Eastern Beringia, a special role belongs to the weevil Lepidophorus lineaticollis. A number of key species of steppe-tundra biota have become relict species. The Pleistocene steppe-tundra was a non-analog ecosystem that formed in the early Pleistocene or slightly earlier and ended in the Holocene. Beetle species migrations across the Beringian Land Bridge were limited by environmental factors and ecological barriers.